Islam as a Religion and Civilization: The Role of Muslim Scholars - Zailani (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2025)
This article examined the profound relationship between religion and Islamic civilization by tracing Islam’s historical, philosophical, and epistemological contributions in shaping an exemplary society (ummatan wāsiṭan). Islam is positioned not only as a spiritual and ritualistic system but also as a civilizational foundation encompassing the domains of knowledge, society, politics, and culture. The Islamic epistemological approaches Bayani, Burhani, and Irfani are explored as theoretical frameworks that integrate revelation, reason, and spiritual intuition. The current article also emphasized the urgency of cultivating Irfani character among Muslim scholars as agents of social transformation who embody scientific excellence, spiritual depth, and social commitment. By upholding the principles of wasatiyyah and the Islamization of studies; this study offered an alternative perspective for constructing a modern Islamic civilization that is just, civilized, and transcendent. The current article concluded by underlining the strategic role of Muslim academics in reconstructing Islamic civilization amid the challenges of globalization and contemporary moral crises.